Histochemical Characterization and Functional Significance of the Hyperintense Signal on MR Images of the Posterior Pituitary - Kucharczyk, John; Kucharczyk, Walter; Berry, Isabelle; de Groot, Jack; Kelly, William; Norman, David; Newton, T. H. (American Journal of Neuroradiology, 1988)
MR imaging of the pituitary fossa characteristically shows a well-circumscribed area of high signal intensity in the posterior lobe on T1-weighted images. We used a combination of high-field MR, electron microscopy, and histologic techniques in experimental animals to determine whether the hyperintensity of the posterior lobe might be functionally related to hormone neurosecretory processes, and to attempt to establish its chemical nature. Histologic sections of a dog's pituitary gland processed with lipid-specific markers showed intense staining in the posterior lobe but not in the anterior lobe, thus documenting the location of fat in the posterior pituitary. Administration of vasoactive drugs known to influence vasopressin secretion to anesthetized cats produced changes in the volume of high-intensity signal in the posterior pituitary. Subsequent electron microscopy showed a significant increase in posterior lobe glial cell lipid droplets and neurosecretory granules in dehydration-stimulated cats. The data suggest that the pituitary hyperintensity represents intracellular lipid signal in the glial cell pituicytes of the posterior lobe or neurosecretory granules containing vasopressin. The volume of the signal may, in turn, reflect the functional state of hormonal release from the neurohypophysis.